Supporting Ph.D. students' skills development: A three-stage doctoral program - Chaló, Paulo; Huet, Isabel; Nikoletou, Dimitra; Pereira, Anabela (Frontiers in Education, 2023)
The promotion of sustainable development is recognized in all educational levels and high-level specialized academic work. In this context, Ph.D. training has begun to be recognized as fundamental to maintaining this workforce of highly specialized academics and professionals leading to an increase in investments in doctoral training which, across Europe, varies significantly by country and university. One of the reasons for this diversity appears to be the absence of literature based on a combination of best practices to support the development of doctoral training programs. This study aimed to contribute to this discussion by combining the perspectives of 31 Ph.D. supervisors and directors from Portugal and England regarding the best practices for Ph.D. training. Participants from different disciplines were interviewed using semi-structured face-to-face interviews and data were analyzed using inductive thematic analysis. Results point out that, even though participants came from different countries, their perceptions about the challenges and strategies for improving doctoral education were convergent. Findings allowed the development of a proposal for structuring doctoral education around a three-stage program. This program’s structure is composed of initial intensive training, assessment of individual needs, and tailored training. Results could prove useful to inform the development or restructuring of Ph.D. programs, intending to address the main needs of Ph.D. students, optimize institutions' resources and promote on-time completion by assuring the timely development of the necessary competencies for the Ph.D. research. Furthermore, this approach is expected to enhance the quality of Ph.D. education, contributing to broadening the spectrum and quality of graduates' competencies and consequently their impact on society, hence contributing to the achievement of the Sustainable Development Goals.